DE-RADICALIZING ISLAMIC CONCEPTS: MAFAHIM YAJIBU AN TUSAHHAḤ AND THE CADREIZATION OF NEO-TRADITIONALIST ULAMA - Muhammad Taufiq; Mulyadi Mulyadi; Sudirman Sudirman (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aims to examine how the teaching of Mafahim Yajibu an-Tushahhah in a pesantren context contributes to the formation of Aswaja-oriented ulama cadres. The study is grounded in the urgent need to strengthen moderate Islamic education in Indonesia amid increasing ideological polarization, religious exclusivism, and digital exposure to intolerant narratives. Pesantren are strategically positioned as educational ecosystems that integrate classical scholarship, moral formation, and community-based religious leadership. This research employed a qualitative approach using a single instrumental case study. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three main results. First, the instructional design of Mafahim learning is systematically structured through prerequisite-based curriculum placement, textual literacy, and the formation of manhajul fikr. Second, its implementation is characterized by dialogical-critical pedagogy, five pedagogical principles, comparative textual analysis, and reflective student outputs. Third, the learning process produces integrated graduate competencies, including theological reasoning, moderation, tolerance, mentoring capacity, and socially responsive religious communication. This study contributes to Islamic education scholarship by proposing a classical text-based moderation pedagogy and recommends that pesantren strengthen progressive curriculum design, dialogical instruction, and competency-based evaluation.